2010
DOI: 10.1371/journal.pone.0015055
|View full text |Cite
|
Sign up to set email alerts
|

Dlk1 Is Necessary for Proper Skeletal Muscle Development and Regeneration

Abstract: Delta-like 1homolog (Dlk1) is an imprinted gene encoding a transmembrane protein whose increased expression has been associated with muscle hypertrophy in animal models. However, the mechanisms by which Dlk1 regulates skeletal muscle plasticity remain unknown. Here we combine conditional gene knockout and over-expression analyses to investigate the role of Dlk1 in mouse muscle development, regeneration and myogenic stem cells (satellite cells). Genetic ablation of Dlk1 in the myogenic lineage resulted in reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
137
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(158 citation statements)
references
References 87 publications
18
137
2
Order By: Relevance
“…We have shown that Dlk1 expression peaks at day 7 following a knife-cut lesion in m. gastrocnemius (Andersen et al, 2009), yet the role of this high Dlk1 induction during muscle regeneration remains to be determined. In agreement with our previous results and those of others (Waddell et al, 2010), we found that DLK1 localizes mainly to interstitial cells (outside laminin + myofibers) ( Fig. 2A) of a nonmyogenic cell lineage (Andersen et al, 2009) (Fig.…”
Section: Dlk1-depleted Heterogeneous Muscle-derived Cell Cultures Exhsupporting
confidence: 93%
See 1 more Smart Citation
“…We have shown that Dlk1 expression peaks at day 7 following a knife-cut lesion in m. gastrocnemius (Andersen et al, 2009), yet the role of this high Dlk1 induction during muscle regeneration remains to be determined. In agreement with our previous results and those of others (Waddell et al, 2010), we found that DLK1 localizes mainly to interstitial cells (outside laminin + myofibers) ( Fig. 2A) of a nonmyogenic cell lineage (Andersen et al, 2009) (Fig.…”
Section: Dlk1-depleted Heterogeneous Muscle-derived Cell Cultures Exhsupporting
confidence: 93%
“…Likewise, diseased and regenerating muscle express high levels of Dlk1, though the number of DLK1 + satellite cells in these scenarios differ greatly, with only very few appearing during muscle regeneration of healthy muscle (Andersen et al, 2009). By contrast, numerous DLK1 + non-myogenic cells emerge in the interstitium between the myofibers upon muscle damage in human and mouse (Andersen et al, 2009;Waddell et al, 2010). Thus, as DLK1 can act in a cell autonomous or non-cell autonomous manner, it may affect myogenic precursor cells regardless of which type of cell expresses DLK1 in the muscle.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence showing that DLK1 may be involved in IGF1 signaling and in muscle growth through Akt phosphorylation (22,(31)(32)(33). We measured Akt phosphorylation in hypertrophic muscles.…”
Section: Significancementioning
confidence: 99%
“…If the point mutation occurs in both the paternal and maternal alleles, it causes no change in DLK1 protein expression (4), which is consistent with the mode of inheritance of the CLPG phenotype. It has been demonstrated that DLK1 protein expression is essential for determining muscle mass (20)(21)(22)(23)(24). Thus, a hypothesis predicting that maternal noncoding RNA might act as a negative regulator of DLK1 expression has been put forth; however, this hypothesis lacks evidence (25).…”
mentioning
confidence: 99%
“…However, loss of Dlk1 expression from the myogenic lineage causes a reduction in muscle mass by reducing myofibre number (Waddell et al 2010). Roles for Rtl1, Dio3 or the ncRNAs in muscle development have not been established, and thus the contribution of Dlk1-Dio3 cluster genes to control of myogenic development has yet to be elucidated.…”
Section: Musclementioning
confidence: 99%